The Influence of Attitude, Subjective Norm, and Behavioral Control on Investment Interest (Case Study on Students of the Faculty of Economics, UNISKA Kediri) - Putri, Bella Anatasya Octavia Ari; Widuri, Trisnia; Nadhiroh, Umi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to examine how Attitudes (X1), Subjective Norms (X2), and Behavioral Control (X3) influence Investment Interest (Y) in students at the Faculty of Economics, Uniska Kediri who have undergone Capital Markets School training. This research uses a quantitative research method with a descriptive approach, by selecting 100 respondents through random sampling. Data collection was carried out using a questionnaire administered via SPSS version 22 software. The process of data analysis encompassed various procedures such as instrument testing, classical assumption testing, multiple linear regression analysis, T test, F test, and coefficient of determination. The findings of the study indicate that Attitudes, Subjective Norms, and Behavioral Control exert a noteworthy impact on Investment Interest among students enrolled in the Faculty of Economics at Uniska Kediri.